The impact of drought stress on the production of spring barley in Poland - Bartosiewicz, Beata; Jadczyszyn, Jan (Polish Journal of Agronomy, 2021)
Recently, the incidence of droughts in Poland has clearly increased. This is a result of the observed climate change, which, according to the most likely scenarios, will have a signifi-cantly perceptible influence on agricultural production. Amongst the observed changes, particularly noticeable is the conspicuous tendency towards an increase in air temperature, solar radiation and wind speed, along with the decrease in precipitation inthe spring–summer period, i.e., in the period of peak water demand. The short growing season and the shallow root system make spring barley sensitive to drought stress. Both the quantity and quality of the yield of this crop depend on the volume and distri-bution of rainfall during the growing season. The water storage capacity of the soil and the plant genotype are equally important. Studies on the influence of drought on the spring barley yields carried out in various scientific centres have demonstrated that the best yields of this cereal are obtained on loamy and silty soils, while the size of the yield is largely limited by water shortage at the end of the vegetative development stage and the beginning of the formation of generative organs. The aim of this work was to summarize the current state of knowledge on the impact of drought stress on the production of spring barley in Poland and to indicate measures compensating for yield losses in drought con-ditions.